Case Report: A large granular cell tumor of the cervical esophagus with single cell RNA sequencing analysis - Shao, Chengying; Chen, Keyu; Duan, Yanting; Xu, Jiajie (Frontiers in Oncology, 2025)
BackgroundEsophageal granular cell tumor (GCT) is a rare benign neurogenic tumor, however, malignant transformation has been reported. And there is no consensus on the choice of esophageal reconstruction in these patients. Therefore, the study of markers of malignant potential in GCT is of great importance in guiding the choice of clinical treatment. Case presentation: Herein, we report the case of a patient with a large cervical esophageal GCT in which a myocutaneous free flap was used to repair a large defect after the resection of a localized esophageal tumor, providing strong reliability in terms of coverage capacity, tissue resistance, and distance management from the recipient vessel. The patient’s recovery was satisfactory at 48 days postoperatively, without significant complications. To further understand the specific cellular status of esophageal granular cell tumors, we performed an in-depth analysis of the tumor and its paraneoplastic tissues in this patient using single-cell RNA sequencing (scRNA-seq), which showed that neural-like cell subpopulations were enriched in the tumor, and genes such as SOX10, S100B, NCAM1, SPP1, and STMN1 were significantly upregulated. A significant copy number variation increase was observed in the X chromosome region. Conclusions: To the best of our knowledge, the present study represents the first scRNA-seq analysis of GCT, providing valuable insights for future prediction of GCT malignancy. In addition, the present study successfully repaired a large cervical oesophageal defect using a skin flap, and these findings have great potential to guide the understanding and management of postoperative large defects in benign cervical esophageal masses, paving the way for further clinical surgical practice in this area.